2016
DOI: 10.15210/sah.v1i1.2609
|View full text |Cite
|
Sign up to set email alerts
|

Anticorpos Contra O Herpesvírus Bovino Tipo 1, Vírus Da Diarreia Viral Bovina E Vírus Da Leucose Enzoótica Bovina Na Região Da Campanha Do Estado Do Rio Grande Do Sul

Abstract: É fundamental para o manejo sanitário dos rebanhos bovinos de leite e corte o suporte de laboratórios especializados como uma ferramenta auxiliar no diagnóstico preciso de doenças infecciosas. O objetivo deste trabalho foi apresentar os resultados dos exames sorológicos realizados pelo Laboratório de Virologia e Imunologia da Faculdade de Veterinária da Universidade Federal de Pelotas entre os anos de 2009 e 2012, na área de bovinocultura de corte e leite. Um total de 6092 amostras de soro bovino foram submeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
4

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
0
5
0
4
Order By: Relevance
“…Chaves et al (2010) reported 61.5% of animals showing Ab-BVDV in Maranhão. Piovesan et al (2013) and Quincozes et al (2007) detected 85.4% and 66.32% of reagents, respectively, in the State of Rio Grande do Sul. In Brazilian's central region, Brito et al (2010) observed prevalence of 64% in the State of Goiás.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Chaves et al (2010) reported 61.5% of animals showing Ab-BVDV in Maranhão. Piovesan et al (2013) and Quincozes et al (2007) detected 85.4% and 66.32% of reagents, respectively, in the State of Rio Grande do Sul. In Brazilian's central region, Brito et al (2010) observed prevalence of 64% in the State of Goiás.…”
Section: Discussionmentioning
confidence: 94%
“…BVDV is responsible for diarrhea, reproductive disorders, mucosal disease and pneumonia. Seroprevalence studies are frequently conducted on adults due to its importance as causative agent of reproductive disorders (Samara et al 2004, Quincozes et al 2007, Brito et al 2010, Piovesan et al 2013, Pasqualotto et al 2015, while researches with calves showing respiratory diseases are uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…Esta ausencia de asociación también fue observada por Gaeta et al (2017b) estudiando becerros pertenecientes a explotaciones familiares, con producción del tipo extensivo. La frecuencia de anticuerpos contra VDVB fue menor que la detectada en otros estados como Maranhão (Chaves et al, 2010), Rio Grande do Sul (Quincozes et al, 2007, Piovesan et al, 2013 y Goiás (Brito et al, 2010). Sin embargo, se encontraron mayores frecuencias de anticuerpos que los encontrados en un sistema extensivo (Gaeta et al, 2018).…”
Section: Discussionunclassified
“…Brazil currently has the largest commercial cattle herd in the world, with 218.2 million animals in 2016 (IBGE 2017). National data obtained from serological surveys revealed a prevalence of BoHV-1 of 42.2% in São Paulo (Mueller et al 1981), 52.9%, 71.3%, and 81.7% in Rio Grande do Sul (Ravazzolo et al 1989, Vidor et al 1995, Piovesan et al 2013. In the state of Minas Gerais, studies conducted in 335 municipalities showed that 93.4% of the animals had positive serology for BoHV-1.…”
Section: Introductionmentioning
confidence: 99%